Agriculture and Water Policy : Toward Sustainable Inclusive Growth - Ahmed, Syud Amer; Gautam, Madhur (World Bank, Washington, DC, 2014)
This paper reviews Pakistan's agriculture performance and analyzes its agriculture and water policies. It discusses the nature of rural poverty and emphasizes the reasons why agricultural growth is a critical component to any pro-poor growth strategy for Pakistan. It supports these arguments by summarizing key results from recent empirical analysis where the relative benefits of agricultural versus non-agricultural led growth are examined. The results also provide an illustration of farm and non-farm linkages. It summarizes recent performance of the agriculture sector, and discusses key characteristics of its sluggish productivity growth. Three key issues related to increasing productivity are discussed: namely technology, water use and water management, and policy reforms related to markets and trade that can strengthen the enabling environment and contribute to the promotion of diversification towards high value agriculture.